2008
DOI: 10.1038/eye.2008.165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Botox® injection treatment for upper eyelid retraction with 6-month follow-up in patients with thyroid eye disease in the congestive or fibrotic stage

Abstract: Aim To compare morphometric data of the eyelid fissure and the levator muscle function (LF) before and up to 6 months after transcutaneous injection with five units of Botox s in patients with upper lid retraction (ULR) from congestive or fibrotic thyroid eye disease (TED). Methods Twenty-four patients with ULR from TED were submitted to transcutaneous injection of 5 units (0.1 ml) of Botox in one eye only. Patients were divided into two groups: 12 with congestive-stage TED (CG), and 12 with fibrotic-stage TED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 15 publications
2
27
0
2
Order By: Relevance
“…Costa et al prospectively studied UER in TED patients treated with BTA, comparing outcomes in patients in the active and inactive phases of the disease 48. They found significant improvement in UER in both groups, with a palpebral fissure height decrease by 3.05 mm in the active group and 3.81 mm in the inactive group.…”
Section: Resultsmentioning
confidence: 99%
“…Costa et al prospectively studied UER in TED patients treated with BTA, comparing outcomes in patients in the active and inactive phases of the disease 48. They found significant improvement in UER in both groups, with a palpebral fissure height decrease by 3.05 mm in the active group and 3.81 mm in the inactive group.…”
Section: Resultsmentioning
confidence: 99%
“…The fibrotic phase required the absence of inflammatory signs and at least 6 months of stable thyroid hormones. 9 Patients who needed systemic steroid treatments were excluded. Changes in the lid parameters after the injection were evaluated separately between those in the congestive phase and those in the fibrotic phase using the ImageJ program 1.42 (National Institutes of Health, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…8,9 The management of the upper lid retraction during the congestive phase of TED is usually limited to conservative treatment. A peribulbar injection of triamcinolone could reduce the inflammatory signs of TED; however, this method is not effective in the lid retraction.…”
mentioning
confidence: 99%
“…In addition, the study by Costa et al found the lid lowering effects of Btx-A lasted longer in patients with fibrotic-stage TED as compared to patients with congestive-stage TED 40 .…”
Section: Induce Ptosis/reduce Lid Retractionmentioning
confidence: 98%